MENINGKATKAN KEMAMPUAN MENULIS RINGKASAN CERITA DALAM PEMBELAJARAN BAHASA INDONESIA MELALUI MODEL SNOWBALL THROWING - HARYATI, SRI (Jurnal Teknologi Pendidikan, 2013)
Classroom Action Research (CAR) is done in the teaching and learning activities for elementary school students 02 Caringin, sub Caringin Bogor Regency to the targets or subjects were 35 students consisted of 16 male students and 19 female students. The fact that investigators found in the teaching and learning activities, most learners do not actively participate in the activities and looks of confusion in starting to make the task given by the teacher so that the impact on the acquisition of learning outcomes, of 35 learners only 8 people or only 22.86% who achieve mastery learning, while 27 percent of students with 77.14% not reached mastery learning or achieving minimum completeness criteria, while the KKM set is 70. To improve the ability, activity, and learning outcomes of students, researchers strive to implement the improvement of learning by using a model of learning by using learning models Throwing Snowball. In the model of snowball throwing (snowballs being thrown), in addition to using instructional media, teachers also apply various methods in learning activities in order to raise the motivation of learners. Motivation is needed for the effective implementation of activities so that students can be active in it and can achieve the expected learning outcomes. Indicators of success in this research is that if students are able to write a summary of the narrative in the sense of a coherent sentence structure and use the rules of writing according to the rules EYD (Spelling Enhanced). This is evidenced by the ability and activities of students during the learning model and throwing snowball at the end of each cycle the average grade achieved was 70 in other words 70% of all learners achieve minimum completeness criteria limit the number by 70. Classroom Action Research is carried out through two cycles, using pre-cycle as a reference which was held on October 22, 2012 followed by a reflection on the results of pre-cycle only 22.86% of participants achieve mastery, then performed the first act in cycle 1 were held on 5 November 2012 continued with reflections on student learning outcomes Cycle 1 began to increase that is 25 people or 71.43% of the 35 learners achieve mastery and 10 people or 28.47% have not reached mastery criteria, but to maximize the action is done both , reflections on the cycle 2, the results obtained by students has increased significantly by 29 people or 82.86% of the 35 learners achieve mastery and only 6 people or 17.14% of the 35 students who have not reached the limit of completeness and need given more intensive guidance, the average value in cycle 2 is 74, the other student activity from one cycle to the next cycle has increased as well. Thus, the ability to write a summary of the story the Indonesian learning can be enhanced by using learning models snowball throwing and hopefully this model can be applied by educators